Determination of Vanadium(IV) and Vanadium(V) in benfield samples by IEC with conductivity detection - Tengku Azmi, Tengku Sharifah Marliza (Springer Link, Vieweg Verlag, 2010)
In this study, the determination of vanadium valence state, V(IV) and V(V) has been achieved using ion-exchange chromatography with conductivity detector. In this method, V(IV) was determined as V(IV)-EDTA complex and V(V) as vanadate ion. Determination of V(IV) was successfully done using 3 mM carbonate/bicarbonate/EDTA at pH 8.6 as the eluent. The additive, EDTA in the mobile phase did not seem to interfere with the V(IV) analysis. The detection of V(V) was achieved with 5 mM disodium hydrogen phosphate buffer at pH 10.4. A linear calibration graph over VO3− and V(IV) with concentration ranges 5–15 mg L−1 gave the detection limit at 0.09 and 0.1 mg L−1, respectively. Both V(IV) and V(V) were successfully determined in Benfield sample, with concentrations of V(IV) and V(V) at 4 and 11,000 mg L−1, respectively.